Isoform Composition and Gene Expression of Thick and Thin Filament Proteins in Striated Muscles of Mice after 30-Day Space Flight. (18th January 2015) - Ulanova, Anna; Gritsyna, Yulia; Vikhlyantsev, Ivan; Salmov, Nikolay; Bobylev, Alexander; Abdusalamova, Zarema; Rogachevsky, Vadim; Shenkman, Boris; Podlubnaya, Zoya
Abstract : Changes in isoform composition, gene expression of titin and nebulin, and isoform composition of myosin heavy chains as well as changes in titin phosphorylation level in skeletal (m. gastrocnemius, m. tibialis anterior, and m. psoas) and cardiac muscles of mice were studied after a 30-day-long space flight onboard the Russian spacecraft "BION-M" number 1. A muscle fibre-type shift from slow-to-fast and a decrease in the content of titin and nebulin in the skeletal muscles of animals from "Flight" group was found. Using Pro-Q Diamond staining, an ~3-fold increase in the phosphorylation level of titin in m. gastrocnemius of mice from the "Flight" group was detected. The content of titin and its phosphorylation level in the cardiac muscle of mice from "Flight" and "Control" groups did not differ; nevertheless an increase (2.2 times) in titin gene expression in the myocardium of flight animals was found. The observed changes are discussed in the context of their role in the contractile activity of striated muscles of mice under conditions of weightlessness.